Translation Techniques Revisited: A Dynamic and Functionalist Approach - Molina, Lucía; Hurtado Albir, Amparo (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThe aim of this article is to clarify the notion of translation technique, understood as an instrument of textual analysis that, in combination with other instruments, allows us to study how translation equivalence works in relation to the original text. First, existing definitions and classifications of translation techniques are reviewed and terminological, conceptual and classification confusions are pointed out. Secondly, translation techniques are redefined, distinguishing them from translation method and translation strategies. The definition is dynamic and functional. Finally, we present a classification of translation techniques that has been tested in a study of the translation of cultural elements in Arabic translations of A Hundred Years of Solitude by Garcia Marquez.